Hydroxystilbenes and methoxystilbenes activate human aryl hydrocarbon receptor and induce CYP1A genes in human hepatoma cells and human hepatocytes - Pastorková, Barbora; Vrzalová, Aneta; Bachleda, Petr; Dvořák, Zdeněk (Food and chemical toxicology, 2017)
Natural polyphenol resveratrol (trihydroxystilbene) is a partial agonist of human aryl hydrocarbon receptor AhR, thereby, displaying a plethora of biological effects. Biological activities of metoxylated and hydroxylated stilbenes were studied in the past. The aim of the current study was to describe the effects of 13 different hydroxy- and methoxystilbenes, including their cis/trans isomers on the transcriptional activity of AhR and the expression of CYP1A genes in hepatic cancer cells HepG2 and in primary human hepatocytes. Techniques of gene reporter assays, qRT-PCR, Simple Western blotting by Sally Sue™ and electrophoretic mobility shift assay EMSA were employed. All compounds activated AhR, but their efficacies, potencies and dose-response profiles differed substantially. The strongest activators of AhR and inducers of CYP1A1 in HepG2 cells were DMU-212 ((E)-3,4,5,4´-tetramethoxystilbene), trans-piceatannol, cis-piceatannol, trans-trismethoxyresveratrol and trans-pinostilbene. While DMU-212 and trans-trismethoxyresveratrol also induced CYP1A1 and CYP1A2 in primary human hepatocytes, the effects of trans-piceatannol, cis-piceatannol and trans-pinostilbene weaned off. On the other hand, trans-4-methoxystilbene was strong CYP1A inducer in hepatocytes but not in HepG2 cells. Differences between effects of stilbenes in HepG2 cells and human hepatocytes are probably due to the extensive phase I and phase II xenobiotic metabolism in human hepatocytes. The data obtained may be of toxicological relevance.
Keywords: kultivované buňky; Basic Helix-Loop-Helix Transcription Factors; Cells, Cultured; Cytochrome P-450 CYP1A1; Gene Expression Regulation; Adult; senioři; receptory aromatických uhlovodíků; Aged; Male; lidé; Cytochrome P-450 CYP1A2; CYP1A1; lidé středního věku; cytochrom P-450 CYP1A2; resveratrol; stilbeny; Humans; cytochrom P-450 CYP1A1; Isomerism; Receptors, Aryl Hydrocarbon; Middle Aged; induktory cytochromu P450 CYP1A2; isomerie; CYP1A2; Stilbene derivatives; Stilbenes; AhR; buňky Hep G2; transkripční faktory bHLH; mužské pohlaví; regulace genové exprese; dospělí; hepatocyty; Resveratrol; Hep G2 Cells; Cytochrome P-450 CYP1A2 Inducers; Cytochrome P450; Hepatocytes